Analisis Faktor-Faktor yang Menjelaskan Penurunan Penjualan Produk BUMdes di Kabupaten Karangasem - Dana, I Gede; Suci, Ni Made (Universitas Pendidikan Ganesha, 2021)
This study aims to (1) extract the factors that explain the decline in sales of BUMDes products in Karangasem Regency, (2) Explain the most dominant factors in influencing the decline in sales of BUMDes products in Karangsem Regency, (3) Explain the factors that affect the decline in product sales BUMDes Karangasem Regency. The results of the factor analysis show that the factors that explain the decline in sales of BUMDes Karangasem Regency are internal factors and external factors. Internal factors consist of decreased product quality, product inventory, higher prices, and decreased promotional activities. External factors consisting of consumers, consumers, and consumers. The factors that most influence the decline in sales are external factors, namely changes in consumer tastes with a rotational varimax value of 0.961. External and internal factors in this study can explain the decline in sales of 72.229% at BUMDes Karangasem Regency.